The input-output analysis for the wholesale and retail trade industry of the Kazakhstan statistics - Kerimkhulle Seyit; Saliyeva Ainur; Makhazhanova Ulzhan; Kerimkulov Zhandos; Adalbek Alibek; Taberkhan Roman (E3S Web of Conferences, 2023)
In this paper has been studied a two-sector input-output model between Wholesale and retail trade industry and Rest of economics. Here, the distribution of the total Input transactions between supply agents of Produce / selling, Gross value added and Import and the distribution of the total Output transactions between Purchase / buying, Final demand and Export consumer agents of the wholesale and retail trade industry create overheating and cooling uncertainty problems of national economy and problems of moderate and critical management of national economy. Particularly identified, – the convergence phase for Produce / selling transactions from 0.577 (or 14.89%) in 1995 to 3.849 U.S. billion dollars (or 14.29%) in 2011 to the state of Equilibrium growth and the divergence phase from 3.779 (or 14.11%) in 2012 to 0.569 U.S. billion dollars (or 3.10%) in 2018 from the state of Equilibrium growth, and also in accordance with the rules of “three sigma” from 24 years of observation in 20 years they were in the cooling zone of the economy beyond the level of critical manageability for flows and for the structure Produce / selling transactions of wholesale and retail trade industry of Kazakhstan economy.